Greenwashing: Evidence from hedge funds - LIANG, Hao (Institutional Knowledge at Singapore Management University, 2021)
We find that a non-trivial number of hedge funds that endorse the United Nations Principles for Responsible Investment indulge in greenwashing. Hedge funds that greenwash underperform both genuinely green and nongreen funds after adjusting for risk. Consistent with an agency explanation, greenwashers (i) underperform more when incentive alignment is poor, (ii) trigger more regulatory violations, and (iii) report more suspicious returns. By exploiting regulatory reforms that aim to enhance stewardship and curb greenwashing, we provide causal evidence that relates agency problems to greenwashing and fund underperformance. Investors, however, do not appear to discriminate between greenwashers and genuinely green funds.